Exploring how ward staff engage with the implementation of a patient safety intervention: a UK-based qualitative process evaluation. Issue 7 (13th July 2017) - Sheard, Laura; Marsh, Claire; O'Hara, Jane; Armitage, Gerry; Wright, John; Lawton, Rebecca
Abstract : Objectives: A patient safety intervention was tested in a 33-ward randomised controlled trial. No statistically significant difference between intervention and control wards was found. We conducted a process evaluation of the trial and our aim in this paper is to understand staff engagement across the 17 intervention wards. Design: Large qualitative process evaluation of the implementation of a patient safety intervention. Setting and participants: National Health Service staff based on 17 acute hospital wards located at five hospital sites in the North of England. Data: We concentrate on three sources here: (1) analysis of taped discussion between ward staff during action planning meetings; (2) facilitators' field notes and (3) follow-up telephone interviews with staff focusing on whether action plans had been achieved. The analysis involved the use of pen portraits and adaptive theory. Findings: First, there were palpable differences in the ways that the 17 ward teams engaged with the key components of the intervention. Five main engagement typologies were evident across the life course of the study: consistent, partial, increasing, decreasing and disengaged. Second, the intensity of support for the intervention at the level of the organisation does not predict the strength of engagement at the level of the individual ward team. Third, the standardisation of facilitative processes provided by the research team does not ensure that implementation standardisation of the intervention occurs by ward staff. Conclusions: A dilution of the intervention occurred during the trial because wards engaged with Patient Reporting and Action for a Safe Environment (PRASE) in divergent ways, despite the standardisation of key components. Facilitative processes were not sufficiently adequate to enable intervention wards to successfully engage with PRASE components.